Evaluation of a nested-grid implementation for 3D finite-difference semi-implicit hydrodynamic models. (February 2015) - Acosta, Mario; Anguita, Mancia; Fernández-Baldomero, F. Javier; Ramón, Cintia L.; Schladow, S. Geoffrey; Rueda, Francisco J.
Abstract: This work evaluates the implementation of a nested Cartesian grid in a 3D semi-implicit hydrodynamic model with synthetic and real examples. The outer model provides all the values needed by the governing equations of the nesting (inner) subdomain at the boundary (including tangential velocities). A 3D flux relaxation scheme is applied to prevent mass and energy drift. The influence of tangential velocities in the solution is evaluated, showing a substantial reduction on the results' quality when they are considered negligible and lateral circulation exists. The inner/outer coupling implemented achieves a simulation time equal to the inner execution time and allows a transfer step equal to the inner time-step, removing time interpolation errors. This coupling makes feasible the 3D relaxation implemented. A dramatic improvement in memory requirements and simulation time is achieved, that allows the use of low-cost low-power consumption platforms in the simulations. Highlights: Nested grid implementation with normal and tangential velocity boundary conditions. Boundary implementation prevent mass and energy drift. Tangential velocities barely affect time and can significantly increase accuracy. Implementation validation with synthetic and real examples shows excellent results' accuracy. Performance evaluation with real examples shows strong reduction in memory and time.